2018
DOI: 10.3390/ma11071098
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Stem Cells Exhibit Different Biological Behaviours in Response to Commercial Bleaching Products

Abstract: The purpose of this study was to evaluate the diffusion capacity and the biological effects of different bleaching products on human dental pulp stem cells (hDPSCs). The bleaching gel was applied for 90, 30 or 15 min to enamel/dentine discs that adapted in an artificial chamber. The diffusion of hydrogen peroxide (HP) was analysed by fluorometry and the diffusion products were applied to hDPSCs. Cell viability, cell migration and cell morphology assays were performed using the eluates of diffusion products. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Diffusion capacity and the biological effects of different commercial bleaching products on human dental pulp stem cells ( h DPSCs) has been evaluated. The findings were that different commercial products with similar HP concentrations exhibited different biological effects on h DPSCs [ 35 ] than similar concentrations of CP and HP.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion capacity and the biological effects of different commercial bleaching products on human dental pulp stem cells ( h DPSCs) has been evaluated. The findings were that different commercial products with similar HP concentrations exhibited different biological effects on h DPSCs [ 35 ] than similar concentrations of CP and HP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to achieve effective dental color alteration in short periods, highly concentrated H 2 O 2 bleaching gels (35-40%) have been traditionally used for professional tooth-bleaching. 1 However, many studies have shown that such esthetic therapy allows diffusion of high amounts of H 2 O 2 through enamel and dentin, 4,5 causing in vitro [6][7][8][9][10][11] and in vivo [12][13][14][15] toxicity to pulp cells. Therefore, the "non-reacted H 2 O 2 " has been considered the main pathway for bleaching-induced tooth sensitivity, claimed by 80-100% of patients undergoing professional tooth-bleaching performed with high-concentrated gels.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][19][20][21] Recent demonstrations show H 2 O 2 from bleaching gels induces pro-inflammatory cytokine release by pulp cells, negatively influencing their long-term regenerative potential. 8,11,14,15,22 Therefore, many alternative therapies have been proposed to increase the biocompatibility of in-office bleaching therapy with the pulp-dentin complex, mainly aimed at reducing the amount of H 2 O 2 capable of reaching pulp cells. 18 Several authors have reported that reducing the H 2 O 2 concentration in bleaching gels and the period of contact of these dental products with enamel may decrease the in vitro and in vivo toxicity caused by these esthetic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Because the tooth is a semi-permeable structure, whitening agents applied at the tooth surface can diffuse and reach the dental pulp, promoting damage to dental pulp cells, such as a decrease in cell viability and metabolism, inflammatory response, DNA damage, apoptosis, or even necrosis [9,10]. These cytotoxic effects are directly proportional to the concentration of HP applied and cell damage relates to tooth sensitivity, the most clinically related adverse effect of tooth whitening [11].…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturers try to overcome this issue by adding desensitizing, stabilizing, or antioxidant agents to the formulation of whitening products, thus promoting protection from oxidative stress for dental pulp cells and preventing tooth sensitivity [12]. However, the exact composition of these products is often unknown, and thus the ability of these other components to protect cells from oxidative stress may vary, contributing to different in vitro and in vivo biocompatibility reports [9].…”
Section: Introductionmentioning
confidence: 99%